Assessment of the Quality of Internet-Based Health Information in the Indonesian Language about Polycystic Ovarian Syndrome: Kajian Kualitas Informasi Kesehatan Berbasis Internet Berbahasa Indonesia tentang Sindrom Ovarium Polikistik - andon hestiantoro; Danang T. Pamungkas (Indonesian Socety of Obstetrics and Gynecology, 2020)
Objectives: To investigate health information quality about PCOS on the internet in Indonesian language.Methods: Top website from two separate search engines (Google and Bing) was collected using the keyword of “sindrom ovarium polikistik” (polycystic ovarian syndrome). Analysis of health information quality on those websites was performed.Results: Sixty-nine websites were included for analysis. The majority of those websites have good information quality in terms of content accuracy and website credibility. There was no difference in quality between the two search engines. The website was found at the top two pages in each search engine to have better quality than the later pages (p=0.02). The educational website had better quality (p=0.05). The website made by healthcare organizations had better quality (p=0.04). The non-commercial website had better information quality (p=0.01).Conclusion: Criteria affecting health information quality on the internet were as follows: found at the top two pages on a search engine; educational website; made by healthcare organization; and non-commercial purpose.Keywords: health information quality, Indonesian language, internet-based, polycystic ovarian syndrome Abstrak Tujuan: Untuk melakukan kajian kualitas informasi kesehatan tentang PCOS di internet dalam Bahasa Indonesia.Metode: Situs web teratas dari dua mesin pencari terpisah (Google dan Bing) dikumpulkan dengan menggunakan kata kunci “sindrom ovarium polikistik”. Analisis kualitas informasi kesehatan pada situs-situs tersebut telah dilakukan.Hasil: Enam puluh sembilan situs web dimasukkan untuk analisis. Mayoritas situs web tersebut memiliki kualitas informasi yang baik dalam hal akurasi konten dan kredibilitas situs web. Tidak ada perbedaan kualitas antara kedua mesin pencari tersebut. Situs web ini ditemukan pada dua halaman teratas di setiap mesin pencari memiliki kualitas yang lebih baik daripada halaman-halaman selanjutnya (p = 0,02). Kualitas situs web berbasis pendidikan menunjukkan hasil lebih baik (p = 0,05). Kualitas website yang dibuat oleh organisasi kesehatan menunjukkan hasil lebih baik (p = 0,04). Situs web non-komersial memiliki kualitas informasi yang lebih baik (p = 0,01).Kesimpulan: Kriteria yang mempengaruhi kualitas informasi kesehatan di internet adalah sebagai berikut: ditemukan pada dua halaman teratas pada mesin pencari; situs web berbasis pendidikan; dibuat oleh organisasi kesehatan; dan tujuan non-komersial.Kata kunci : bahasa indonesia, berbasis internet, kualitas informasi kesehatan, sindrom ovarium polikistik.